BETTER UNDERSTANDING THE 4THMARKET OF CHILDREN AS CONSUMERS - jony Oktavian Haryanto (FIRM Journal of Management Studies, 2020)
Children are a big market with great potential. As reported by www.quora.com, for just the clothing market, the children’s market is approximately US$ 173.6 billion dollars. Some studiesrevealed that the market total for children reaches 80 billionUSD annually for 2019. According to Haryanto et al. (2015), the children’s market consists of three simultaneous markets, which are: First, the primary market, where children spend their money to purchase the products they like. Children’s spending is reflected from the data on the pocket money that is given to them by their parents. Data in Indonesia that was surveyed from TotalyAwesome (a child-friendly advertisement and digital content platform) in 2016-2017 showed that for children between the ages of 4 and 14 years old, they receive an average monthly allowance of Rp 550,000. The money is mostly spent for meal (No. 1), drinks (No. 2), toys (No. 3), and snacks and books (No. 4)